Dietary protein requirement of stunted fingerlings of rohu, Labeo rohita (Hamilton) during grow-out stage - Kumar, R V; Ramesh, K S; Patil, Prakash; Kumar, B T Naveen; Manissery, Joseph K (Indian Journal of Fisheries, 2012)
The aim of the study was to determine the optimum dietary protein requirement in the diets of stunted fingerlings of rohu in grow-out stage. Stunted rohu (Labeo rohita) fingerlings (5 g average weight) were stocked in manured cement cisterns, with 80 Â± 2 cm water column and fed formulated diet having 20% (T1), 25% (T2) and 30% (T3) protein in triplicate. Fishes stocked in three manured cisterns without supplementary feed served as control (T0). Water quality parameters viz., temperature, pH, dissolved oxygen, carbon dioxide and alkalinity recorded in different treatments did not differ significantly. The final average net weight recorded in T0, TI, T2 and T3 were 128.39 g, 141.81 g, 178.29 g and 148.61 g respectively, after a rearing period of 120 days. The growth of fish was significantly (p<0.05) higher in 25% protein (T2) diet than in the other treatments. The carcass proximate composition of rohu did not show any significant difference between treatments and the control. The results indicated that the diet containing 25% crude protein was optimum in terms of weight gain (g), specific growth rate (SGR) (% day-1) and feed conversion ratio (FCR) for stunted fingerlings of rohu during grow- out stage in the presence of natural food.